Subaltern Voice and the Politics of Representation - Saradar, Satya Narayan (Journal of Kathmandu BernHardt College, 2024)
Subaltern is a term coined after to discuss the state of marginalized and suppressed people existing in our society. They have been far away from the main stream discourse. They are fully controlled and suppressed by the elites. On the other hand, the subaltern has been the issued of various people to bring forward and create a ground for discussion. This term has come in existence since the postcolonial era. The wide discussion on subaltern has given a big platform to understand the underprivileged group. The society consists the subaltern but their voice is suppressed or they are totally ignored in mainstream discussion. Subalterns have been the stairs for the elites to grow and gain in the society. In the name of representation, again subalterns are dominated and others get benefitted.